Influence of intra-mammary ozone administration on udder health in herds with contagious mastitis in the context of management practices - Koseman, A.; Seker, I.; Risvanli, A. (Polska Akad Nauk, Polish Acad Sciences, Univ Warmia & Mazury Olsztyn, 2019)
This study investigates the effectiveness of intra-mammary ozone administration in the dry period and at the time of delivery for preventing against mastitis in herds with contagious mastitis. The cows were divided into five groups with 10 cows in each. Group 1 was administered an ozone-containing foam preparation via the teat canal into four udder quarters for 5 seconds at the beginning of the dry period; Group 2 was administered ozone at the beginning of the dry period and at the time of delivery; Group 3 was administered ozone at the time of delivery; Group 4 was administered a dry period udder preparation at the beginning of the dry period; and Group 5 was administered only teat seal at the beginning of the dry period. No statistically significant difference was found between the cows with regard to the SCC values at the beginning of the dry period and at the time of delivery (in cows without clinical mastitis, n=25). The SCC values were reported to decrease when the values at the beginning of the dry period and at the time of delivery were compared. All cows except two in Group 1 were detected to have clinical mastitis according to the frequency of microbial isolation in milk at the time of delivery. In conclusion, intra-mammary ozone administration did not prevent mastitis in the dry period or at the time of delivery in herds with contagious mastitis; moreover, it was determined to increase the rate of clinical mastitis in the postpartum period.
Keywords: prevention; mastitis; management; microbiological analysis; ozone